Transformation and Features of Plant Successions of the Taman Peninsula in Case of Technogenic Impact - Litvinskaya Svetlana (Russian Journal of Earth Sciences, 2023)
The impact of technogenic objects on the plant communities of the Taman Peninsula is considered. Technogenic transformations lead to destabilization of the balance in plant communities and landscapes of the Taman Peninsula. Anthropogenic successions are manifested differently in different types of ecosystems. The speed and nature of these processes usually determine the resistance of individual populations to the action of new environmental factors on them. When the vegetation cover is destroyed, the succession will focus on the formation of a ruderal community. When the sand-shell substrate was replaced with cement blocks in the littoral zone, the succession began to form linear synanthropic communities.